If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying P(p + -3) + -6p + -18 = 0 Reorder the terms: P(-3 + p) + -6p + -18 = 0 (-3 * P + p * P) + -6p + -18 = 0 (-3P + pP) + -6p + -18 = 0 Reorder the terms: -18 + -3P + -6p + pP = 0 Solving -18 + -3P + -6p + pP = 0 Solving for variable 'P'. Move all terms containing P to the left, all other terms to the right. Add '18' to each side of the equation. -18 + -3P + -6p + 18 + pP = 0 + 18 Reorder the terms: -18 + 18 + -3P + -6p + pP = 0 + 18 Combine like terms: -18 + 18 = 0 0 + -3P + -6p + pP = 0 + 18 -3P + -6p + pP = 0 + 18 Combine like terms: 0 + 18 = 18 -3P + -6p + pP = 18 Add '6p' to each side of the equation. -3P + -6p + 6p + pP = 18 + 6p Combine like terms: -6p + 6p = 0 -3P + 0 + pP = 18 + 6p -3P + pP = 18 + 6p Reorder the terms: -18 + -3P + -6p + pP = 18 + 6p + -18 + -6p Reorder the terms: -18 + -3P + -6p + pP = 18 + -18 + 6p + -6p Combine like terms: 18 + -18 = 0 -18 + -3P + -6p + pP = 0 + 6p + -6p -18 + -3P + -6p + pP = 6p + -6p Combine like terms: 6p + -6p = 0 -18 + -3P + -6p + pP = 0 The solution to this equation could not be determined.
| 7y(3x+2y)= | | 8/14x=6/10 | | 8/14=6/10 | | 28y-187=15x | | 5/9x=60 | | 7p^2-12p-2=5p-8 | | -2x+8=3x+10 | | 63=6n+3n-2n | | 15y+187=28x | | 6h^2+26h-2=-10 | | 0.36*(11/2) | | x^5+540=0 | | 2.5x+2.8=-1.2x+9.8 | | F(x)=8-2x-x^2 | | (x+6)=2(1-x) | | 2.3x+2.8=-1.3x+9.8 | | 4m+5m-9=3m+m+6 | | 6k^2+k-12=0 | | 4x-3/5x÷4x^2-5/5 | | x^5-x^4-x^3+x^2-2x+2=0 | | 2.5x=11+3x | | X^2-9x-56=0 | | r/2-r/3=3 | | cot^2(x)=3 | | 25/4=R/5 | | 4y^2=400 | | .1*.56*x+.5x=48000 | | 2(4m-2)-4=-64 | | 4a-6a^3=0 | | 42*1/2 | | 2e+3=7e+2 | | 2(7x-4)=5(2x+4) |